The ceo-d index and its relationship with oral health-related quality of life in preschool children of the I.E. César Vallejo, Chorrillos, June 2018 - Rocha Lerzundi, Joel Maycol (2019)
Objective: To determine the relationship between the ceo-d index and the oral health-related quality of life (OHRQoL) in preschool children of the I.E. César Vallejo, Chorrillos - 2018.  Materials and methods: An observational and cross-sectional study, which evaluated 118 children aged 3 to 5 who registered dental caries according to the ceo-d index and the ECOHIS survey for the perception of oral health-related quality of life. The statistical tests used in the research were the Student´s t test, Kruskal-Wallis H test and Mann-Whitney U test, with a significance level of 0.05 and a Spearman coefficient of 0,01.  Results: The average of the ceo-d index was 6,60 ± 3,95, which indicates a very high level of severity, and a frequency of 88.98 %. The ECOHIS survey showed a negative impact (21,72 ± 14,15) and a high frequency (85.59 %) on the oral health- related quality of life. The most frequent dimension was "functional limitation" (83.90 %). According to the Spearman coefficient, there is a significant moderate positive direct relationship (r = 0,682) between the variables "dental caries" and "quality of life". This relationship prevails in the female (21.83 ± 12.56) and 5-year-old (33.67 ± 11.17) groups,, both of which were statistically significant (p = 0.000). Conclusions: Dental caries generate a negative impact on the quality of life that affects the various activities of children, and has repercussions on their family and environment. The larger the number of dental caries and severity, the greater negative impact on the quality of life. This condition worsens with increasing age, and girls are more prone to have it.